Pemanfaatan Lingkungan Sekolah sebagai Media Pembelajaran untuk Meningkatkan Hasil Belajar Mata Pelajaran Geografi Siswa Kelas XI IPS-1 SMA Negeri 6 Mataram - Sriwidiastuti, Putut (Lembaga Yasin AlSys, 2023)
The aims of this study were to find out: 1) Improving the learning outcomes of class XI IPS-1 students at SMA Negeri 6 Mataram in the subject of Geography by using learning media in the school environment for the 2022/2023 school year; 2) Improving the learning activities of class XI IPS-1 students of SMA Negeri 6 Mataram during the learning process in Geography subject by using school environment learning media. This research method uses Classroom Action Research (CAR). The subjects of this study were all 33 students in class XI IPS-1 at SMA Negeri 6 Mataram in the odd semester of the 2022/2023 academic year. The instruments used were: observation sheets of teacher and student activities and the rubric of student creativity using percentage analysis. Based on the results of the data analysis, it was found that: Utilization of the school environment as a learning medium in the Geography subject, the subject matter of flora and fauna in Indonesia and the world can improve student learning outcomes for class XI IPS-1 SMA Negeri 6 Mataram. This is evidenced by the research data for two cycles. Prior to the research, the percentage of completeness of student learning outcomes only reached 36.36%. In cycle I, student learning outcomes increased to 69.70% and in cycle II it reached 93.94%. Utilization of the school environment as a learning medium can also increase student activity during the learning process. Student activity in cycle I and cycle II reached 62% and 88%, respectively. Thus, from the description above, it can be concluded that the use of the school environment as a learning medium can improve learning outcomes in the Geography subject for Class XI IPS-1 SMA Negeri 6 Mataram Odd Semester in the Academic Year 2022/2023 and it can be said to be successful.